Influence of zinc oxide nanoparticles on the mechanical and thermal responses of glass fiber‐reinforced epoxy nanocomposites. Issue 1 (2nd August 2019) - Thipperudrappa, Sridhar; Ullal Kini, Achutha; Hiremath, Anupama
Abstract: The present article investigates the effect of incorporation of zinc oxide (ZnO) nanoparticles in varied weight percentages into glass fiber‐reinforced (GFR) epoxy composites through the evaluation of mechanical properties such as flexure strength, impact strength, and ultimate tensile strength of the composite. Thermo‐gravimetric analysis for the fabricated composites has been taken up to evaluate the effect of ZnO nanoparticle on the thermal stability of the composite. The ZnO nanoparticle is loaded in different weight percentages ranging from 1 to 5 wt% and is dispersed uniformly in the epoxy resin through ultrasonication method. The required GFR epoxy‐ZnO nanocomposites are fabricated through hand layup technique and cured through vacuum bagging method. The analysis of the obtained result indicate that ZnO has a negative impact on the mechanical properties such as flexure and tensile strengths, while it had a positive impact on the impact strength of the GFR epoxy‐ZnO nanocomposites. These results indicate that ZnO has a greater affinity with the epoxy resin, which results in increase in matrix‐dominated properties. The presence of ZnO nanoparticles result in the reduction of active sites for bond formation between the matrix and the glass fibers which tends to reduce the fiber‐dominated properties such as tensile and flexure strength. The thermal responses of GFR epoxy‐ZnO nanocomposites increased up to 2 wt% addition of ZnO nanoparticles, while at 5 wt% there was a reduction in the thermal response of the nanocomposite due to an increased steric hindrance.